2010
DOI: 10.1038/jcbfm.2010.15
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Volume Alterations in the Perilesional Areas in the Rat Brain after Traumatic Brain Injury—Comparison with Behavioral Outcome

Abstract: In the traumatic brain injury (TBI) the initial impact causes both primary injury, and launches secondary injury cascades. One consequence, and a factor that may contribute to these secondary changes and functional outcome, is altered hemodynamics. The relative cerebral blood volume (CBV) changes in rat brain after severe controlled cortical impact injury were characterized to assess their interrelations with motor function impairment. Magnetic resonance imaging (MRI) was performed 1, 2, 4 h, and 1, 2, 3, 4, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 42 publications
4
27
0
Order By: Relevance
“…3). In accordance with the view that perfusion compromise is linked to functional deficits (Bonne et al, 2003;Immonem et al, 2010), we found that the reduction of hypoperfusion area was associated with the augmentation of functional recovery as evaluated by mNSS (compare Fig. 3G with Fig.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…3). In accordance with the view that perfusion compromise is linked to functional deficits (Bonne et al, 2003;Immonem et al, 2010), we found that the reduction of hypoperfusion area was associated with the augmentation of functional recovery as evaluated by mNSS (compare Fig. 3G with Fig.…”
Section: Discussionsupporting
confidence: 68%
“…As found in the present study, MSCs diminish hemodynamic abnormalities (Fig. 3G) by early restoration of blood flow perfusion to deliver oxygen and glucose, which may rescue neurons at risk from energy deprivation (Immonem et al, 2010). The ability of MSCs to facilitate vascular remodeling (Borlongan et al, 2004), to enhance neurogenesis (Mahmood et al, 2004b), to protect neurons (Wilkins et al, 2009) and to support axonal regeneration (Ankeny et al, 2004), which in turn moderate neuropathological change and white matter degeneration, may contribute to tissue preservation (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Previously, it was found that different cortical contusion zones ranging from the injury center, through its periphery, to the surrounding penumbra, display specific pathological characteristics, e.g., blood flow and oxygenation, in both human and experimental TBI. [43][44][45][46][47] Considering the dependence of mitochondrial structure and energetics on the availability of biofuel and oxygen, the differences in mitochondrial morphology among these zones is consistent with these gradients.…”
Section: Discussionmentioning
confidence: 96%
“…Thomale et al 20 found severe hypoperfusion (by laser Doppler flowmetry) in the area of the impact at 0.5-6.0 hours and hyperperfusion at 24 and 48 hours in a similar rat model of moderate CCI. Immonen et al 21 found that cerebral blood volume dropped 1 hours after injury, pseudonormalized on days 1-3 and increased on day 4 in a similar CCI model. Other studies found CBF reduction on day 0 using the Marmarou rat model 6 or fluid percussion model 22 but without hyperperfusion on subsequent days after TBI.…”
Section: Cortical Blood Flowmentioning
confidence: 99%